Restoration of Gene Function by Homologous Recombination: from PCR to Gene Expression in One Step - Yosef, Ido (American Society for Microbiology, 2004)
We have developed a simple method for single-step cloning of any PCR product into a plasmid. A novel selection principle has been applied, in which activation of a drug selection marker is achieved following homologous recombination. In this method a DNA fragment is amplified by PCR with standard oligonucleotides that contain flanking tails derived from the host plasmid and the complete λP(R) or rrnA1 promoter regions. The resulting PCR product is then electroporated into an Escherichia coli strain harboring both the phage λ Red functions and the host plasmid. Upon homologous recombination of the PCR fragment into the plasmid, expression of a drug selection marker is fully induced due to restoration of its truncated promoter, thus allowing appropriate selection. Recombinant plasmid vectors encoding β-galactosidase and neomycin phosphotransferase were constructed by using this method in two well-known Red systems. This cloning strategy significantly reduces both the time and costs associated with cloning procedures.